“What it means to be a woman:” Ambivalent sexism in female college students’ experiences and attitudes - Fields, Alice M. (2013)
This study used content analysis to examine if themes related to ambivalent sexism (Glick and Fiske 1996) emerged when female students wrote an essay answering the question “What does it mean to be a woman?” and examined the relationship between Ambivalent Sexism Inventory (ASI) scores (Glick and Fiske 1996) and content analysis. Participants were 78 female undergraduate students in the Southeastern U.S. Findings revealed themes related to ambivalent sexism were present in 99% of essays, indicating that ambivalent sexism is highly relevant to women’s gendered experiences. Furthermore participants’ ASI scores were positively correlated with a sexism score created from coded essay content. The discussion addresses theoretical and contextual implications of the findings.